Trade, externalities, and the impact of asymmetric information on trade policy - Giuseppe Francesco Gori; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper investigates the relationship between trade liberalisation, consumers' environmental awareness and a negative environmental externality in consumption. We adopt an international Hotelling duopoly setup, where firms are located in two asymmetric countries. We find that, if the intensity of environmental externality is common knowledge for country governments, this setup delivers no need of accompanying trade policies in order to enforce trade liberalisation. In the opposite case, in which information is asymmetric, i.e., the small country's Government cannot observe the positive enviromental effects of its firm's exports to foreign consumers, we find that: (i) the Pareto optimum is always enforced, since the brown country always relaxes the distortionary trade policy, and (ii) cheating on the environmental externality allows the brown country's government to extract extra surplus from the green country. Allowing for trade in green technology delivers opposite conclusions: the externality is minimised and welfare is maximised in equilibrium if information is symmetric while trade liberalisation with asymmetric information always entails a second best outcome.
Keywords: F12; L13; H23; 330